A survey of Old Testament introduction - Archer, Gleason Leonard, 1916- (Chicago, IL Moody, 1974)
Includes bibliographical references and indexes.
Donated from the library of Mr John Fraser Dickson, November, 2002.
Keywords: Bible. O.T. -- introductions